PENGARUH STRATEGI PEMBELAJARAN BERDIFERENSIASI DENGAN MODEL PBL TERHADAP HASIL BELAJAR PESERTA DIDIK - Kurniawan, Damasus Jeki; Sitompul, Stepanus Sahala; Firdaus, Firdaus (Universitas Tanjungpura, 2025)
The purpose of this study is to examine if differentiated learning techniques utilizing the PBL model on vibration and wave content improve student learning results at SMP Negeri 1 Sungai Raya. The study design was One Group Pretest-Posttest with a class VIII population, and the sample size was 32 students from class VIII G. This study tool use a test to enhance student learning results. Data analysis is utilized to identify the rise in student learning outcomes before to and during therapy, as well as the increase in student learning outcomes by category. According to the data analysis conducted in this study, there was an increase in student learning outcomes for vibration and wave content taught utilizing the PBL paradigm with differentiated learning techniques. The average score for student learning outcomes before and after implementation was 36.08 and 81.31, respectively. The medium category's N-Gain score of 0.69 also indicates an improvement in learning outcomes. The use of differentiated learning techniques utilizing the PBL paradigm to improve learning outcomes received a score of 80.5, placing it in the excellent category. Based on the findings of this study, it is envisaged that differentiated learning techniques employing the PBL paradigm may be used in the scientific learning process.